Stroke rehabilitation in low resource countries: time to provide an organised service - Mehran Maanoosi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
Introduction: Stroke is one of the leading causes of death and disability in low- and middle-income countries (LMICs). The proven efficacy for rehabilitation interventions in improving stroke outcomes in LMICs supports the need to strengthen the rehabilitation workforce. Low-cost physical rehabilitation interventions requiring minimal resources, self-rehabilitation, tele-rehabilitation and involvement of family and other carers can be a solution and improve functional outcomes. Method: A literature search using the terms Stroke and Rehabilitation were carried out by the Chief Librarian at St. Richard's Hospital, the University Hospital Sussex. Four databases, namely Ovid Medline, EMBASE, CINAHL and Ebsco CINAHL, were searched using appropriate subject headings and free text terms such as stroke and rehabilitation . We used free text terms to look for concepts synonymous with rehabilitation in LMICs. We did not search for individual countries or continents/sub-continents. Results: Relevant results from 2015 to current were included. Twenty articles were finally chosen which included the most relevant and useful information for the purpose of this article. Conclusion: Populations in LMICs are exposed to health systems which do not include rehabilitation services. In addition, there are personal barriers to accessing quality stroke rehabilitation that could improve stroke survival and functional outcomes. Although there have been some improvements in the development of stroke rehabilitation in some LMICs, further investment is required to ensure that LMICs continue to receive the best quality rehabilitation services. There are measures that can be put in place to reduce these deficiencies. Collaboration between LMICs and developed countries has been growing but this needs to be extended, especially in training doctors in Rehabilitation Medicine and upskilling therapists. The World Health Organisation Rehabilitation 2030 is an action plan to scale up rehabilitation so that countries, especially LMICs, can be better prepared to address the evolving rehabilitation needs of populations by 2030.